Thailand Economic Monitor, January 2019 : Inequality, Opportunity and Human Capital - World Bank Group (World Bank, Bangkok, 2019)
The outlook for the global economy has darkened amid elevated trade tensions. International trade and investment are moderating, trade tensions remain elevated, and financing conditions are tightening. Global growth is projected to moderate from a downwardly revised 3 percent in 2018 to 2.9 percent in 2019 and 2.8 percent in 2020-21, as economic slack dissipates, monetary policy tightens in advanced economies, and global trade gradually slows (World Bank Global Economic Prospects, January 2019). Despite external shocks to trade and tourism, growth of the Thai economy is estimated to have accelerated to 4.1 percent in 2018. The economy proved to be resilient in the face of strong global headwinds due to strengthening domestic demand stemming from an upswing in private consumption and private investment. Domestic consumption expanded by 5 percent in 2018Q3, posting the highest growth rate in 22 quarters in a low-inflation environment and record-low unemployment. In addition, private investment grew by 3.9 percent in the third quarter supported by increased spending on construction, machinery and equipment. Strong domestic demand offset partially adverse global factors—the China-US trade dispute—as well as domestic and idiosyncratic factors—such as the Phuket boat tragedy and the high-base effect of gold exports. The Thai economy also owed its resiliency to strong and stable macroeconomic fundamentals.